Urban notes. Conscious and participatory drawing - Bruno Seve; Ernest Redondo Domínguez; Zaida Muxi Martínez (EGA, 2023)
Graphic representation in architecture has been drastically transformed with the arrival of new technologies. In this changing contemporary context, freehand drawing’s role and objectives are being reconsidered as an aesthetic goal and as a pedagogical process. The way we transform our urban spaces is also evolving, with increasingly participatory approaches that include diverse perspectives. In search of alternative, innovative learning methods, this article shows the results of Urban Notes, an elective community activity in which students, associations and neighbourhoods exchange ideas about the place through urban drawing. First, a theoretical background is proposed that supports Urban Notes use as a participatory urban exploration tool, and then recent experiments are described. The results reveal a new form of transdisciplinary learning for schools of architecture and urbanism.